Translating Cultural References: Approaches and Challenges in Student Self-Translations of Indonesian Short Stories into English - Sihite, Meida Rabia; Sari, Winda Setia; Siregar, Masitowarni; Tangkas, I Wayan Dirgayasa (ICONELT, 2024)
Translation has become essential for communication between cultures in our globalized world. This research investigates how the student translators translate Indonesian short stories into English, mainly on cultural references such as idiomatic expressions and customs, using methods to find out the approaches and challenges they face. While essential to narrative validity and cohesion, these features present their challenges. This research, then, investigates domestication (making the text familiar to the target) and foreignization (keeping original cultural elements) through qualitative case studies with content analysis and interviews. Results indicate that students apply domestication to obtain a more readable text, even at the cost of some cultural content. Even when it comes to translating food items or slang, they have somewhat of a shallow character in most cases. At the same time, personal names and some religious terms were preserved to avoid cultural and identity loss. Significant obstacles are dealt with in this study as the linguistic variety is taken into consideration and the cultural aspect of translators dealing with their strategies. It advises the usage of both domestication and foreignization in translation education, enhancing reflexivity and increasing familiarity with translation tools. Specifically, workshops on cultural competency and idiomatic expression are recommended for improved praxis. The empirical findings contribute to the understanding of literary translation by inviting further investigations across languages and genres. These insights can then help us create better translation practices and education that will theoretically cover the gap between cultures through literary works.